Eco-friendly natural rubber latex and modified starch-based adhesive for wood-based panels application- A review - Soubam, Triveni; Gupta, Arun (School of Renewable Energy, Maejo University, 2021)
The use of formaldehyde-based synthetic adhesives for the development of wood-based panels has increased rapidly in the industry. Synthetic adhesives are regarded as a threat to human health and a pollutant because they emit formaldehyde's carcinogenic gas. The breakthrough has prompted to seek for a long-term solution to the formaldehyde threat with natural resources. There has been a significant rise in bio-based adhesive technology and development in the wood-based panel industry. The current review article is intended to present the potentials and the drawbacks of the development of bio-adhesives from sustainable resources such as natural rubber latex (NRL) and starch. This review also discussed the chemical modification and crosslinkers of starch to improve water resistance and adhesion properties. Moreover, this article discusses the compatibility of modified rice starch and NRL for their conclusive applications as wood-based panels adhesive. The findings suggested that bio-based adhesives could replace more synthetic-based adhesives with comparable performance in the near future.